Psikolinguistik, Neurolinguistik, dan Metafora Kognitif Komputer dalam Perkembangan Bahasa Teknologi Kecerdasan Buatan - Maulida, Siti Zumrotul; Aidha, Fakhriyyah Asmay; Khoirunnisa, Krismonika (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The study aims to identify the psychology of language development in artificial intelligence technology systems. The study USES qualitative descriptive methods that will be used to analyze the results of paraphrased students' handwriting using the three artificial intelligence apps Chat GPT, Aizzy AI, and Perplexity AI. The data analysis on this research is based on text and narrative based on its semantic building structure, morphology, and syntax. The data processing process on this research uses simple searches related to specific keywords to get paraphrasing results from all three applications of artificial intelligence. The result of this study was the discovery of significant differences. The significance found is the language processing of the paraphrased text using the same keyword search, both of which use Chat GPT, Aizzy AI, and Perplexity AI.